Strategi Media Promosi Katalog Produk Berbasis Adobe Photoshop untuk Meningkatkan Minat Beli Konsumen di Koffeein Surabaya - Abimanyu Arya Pradana; Umi Khabibah; Suci Nurfauziah (Fakultas Ekonomi & Bisnis, Univ, 2026)
Koffeein Surabaya is a business engaged in the field of food & beverages that carries the theme of Coffee Shop and is located on Jalan Pucang Anom Timur 4 No. 26A. Koffeein Surabaya is less than optimal and has not reached the target market. Therefore, promotional media in the form of a product catalog in the form of printed media is needed, so this study aims to help create a product catalog in order to increase purchasing interest for consumers and potential consumers. This study is an Action Research and uses Adobe Photoshop as a product catalog creation application. Measurement of the effectiveness of the product catalog in this study uses EPIC and AIDA indicators. Data collection methods used are observation, interviews, questionnaires and documentation. The finished product catalog design is then evaluated by distributing questionnaires to 2 IT experts, 2 marketing experts, 1 owner and 15 consumers and potential consumers. The measurement of product catalog effectiveness in this study uses the EPIC and AIDA indicators. This study has gone through two cycles, cycle 1 showed that the product catalog was still not good enough so it needed to be continued to cycle 2. In cycle 2, the Koffeein Surabaya product catalog was said to be good and feasible with an EPIC rate score of 4.41 in the very effective category and an AIDA analysis method of 86.62 in the very good category. From this study, it can be concluded that the product catalog is said to be effective, good, and feasible to be used to help develop and provide promotional media for Koffeein Surabaya as an effort to increase consumer purchasing interest.